Potencial tóxico, citotóxico e mutagênico de extratos aquosos de Licania rigida (Chrysobalanaceae) em células in vivo - Melo, Naama Jessica de Assis (Universidade Federal Rural do Semi-Árido, 2015)
The species Allium cepa is widely used in studies such as biological indicator of toxicity and can be affected by other plant extracts through allelopathy. Many toxic plants of livestock interest have allelopathic compounds and cause damage to animal health. Among these plants is Licania rigida (oiticica). The objective of this study was to evaluate the toxic and cytotoxic effects of L. rigida extracts in bulbs of A. cepa. The bulbs were incubated in distilled water (negative control) and at concentration 5 mg/L, 50 mg/L and 300 mg/L of aqueous extracts of dried and fresh leaves. It was evaluated the root growth and relative inibition. With the bulbs blades were made of meristematic root cells for the evaluation of cytotoxicity. The extracts of the dry and fresh leaves in bulbs caused inhibition at concentrations of 5 mg/L and 300 mg/L, while the concentration of 50 mg/L stimulated. It was not observed cytotoxic activity of the aqueous extracts of dried and fresh leaves, because there were no statistically significant differences
Toxic, cytotoxic and mutagenic potencial of the aqueous extracts of Licania rigida (Chrysobalanaceae) in cells in vivo
Keywords: Alelopatia; Citotoxicidade; Crescimento; Allelopathy; Cytotoxicity; Growth; CIENCIAS AGRARIAS::ZOOTECNIA